Ergonomic Analysis of UI’s BicyclesUsing Posture Evaluation Index (PEI) Method in Virtual Environment - Muslim, Erlinda; Nurtjahyo, Boy; Zulkarnain, Zulkarnain; Afrinotha, Liza (Makara Journal of Technology, 2010)
Ergonomic Analysis of UI’s Bicycles Using Posture Evaluation Index (PEI) Method in Virtual Environment. This research was conducted to study the ergonomic aspect of University of Indonesia’s bicycles in virtual environment. Software Jack 6.0 was used to analyze it. PEI was used as an approach that integrated the results of three methods: lower back analysis (LBA), ovako working posture analysis (OWAS), and rapid upper limb assessment (RULA). The research objective is to evaluate the existing design of University of Indonesia’s bicycles and to determine the most ergonomic redesign which concerns handlebar height and saddle height modification. The result showed that the most ergonomic design of University of Indonesia’s bicycles is the one with the highest handlebar height (22 cm) and the lowest saddle height (11 cm).